Theoretical foundations of honour-based violence. Review of the state of the art - Montoya Rodríguez, María Victoria Steffany; Villacampa Estiarte , Carolina (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2025)
Honor crimes are a form of violence committed to restore family or community honor through punishment, in the face of non-compliance with norms of sexual conduct imposed on women for cultural, religious or gender-based reasons. This research presents the results of a systematic review conducted in two databases -Scopus and WoS- on literatura published between 2016 and 2023 about the theoretical foundations of honor-based violence, composed of 40 articles. The results reveal the complex interaction between cultural traditions, religious parameters and patriarchal socialization archetypes that legitimize this violence and identify two types of approaches. On the one hand, the culturalist ones, which conceive it as an expression of religious traditions and mandates, by virtue of which these crimes are either justified by the community, leading to the attenuation or exclusion of criminal responsibility, or are criminally repudiated, leading to the segregation of these cultures. On the other hand, those who characterize it as a manifestation of gender violence as well as a serious attack on human rights, attributing its production to patriarchal systems of gender discrimination, who propose the criminal prosecution of those who practice it. It is concluded that, although the majority characterize it as gender violence, there is consensus that the institutional response should not perpetuate the oppression of the women who suffer it, but rather promote respect for local forms of resistance that foster their autonomy. Thus, in addition to the criminal proscription of honor crimes, preventive and culturally sensitive state